The Educational Planning and Development - Tin Moh Moh Swe; Hadiyanto Hadiyanto; Yahya Yahya (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
A directed education process will bring this nation towards a better civilization. Conversely, an educational process that is not directed will only take up time, energy and funds without any results. Thus, the education system as the implementation of national education greatly determines the progress of a nation. To realize the goals of education, it is necessary to carry out planning and development in the world of education which continues to move forward by utilizing familiar technology in the 4.0 era. Planning is something that is important before doing anything else. Planning is considered important because it will determine and at the same time give direction to the goals to be achieved. Thus a work will be messy and undirected if there is no proper planning, careful and well-organized planning will have an impact on the achievement of educational goals that have been programmed. In addition, development can also determine the success or failure of a program, programs that do not go through good planning, then development tends to fail. The method in this research is literature review, namely by reviewing books and journals in accordance with the theory discussed in the article theme, namely to carry out in-depth discussions regarding Educational Planning and Development so that it can run optimally. Keywords: Planning, Development, Education